SOCIAL MEDIA ASSISTED LANGUAGE LEARNING (SMALL) FOR READING CLASSROOM : EFL LEARNERS’ PERCEPTION - Fatin Nadifa Tarigan; Siti Aminah Hasibuan; Alwi Fahruzy Nasution (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
Addressing the issue of the dynamics of social media as tool for learning, the present study aims at investigating the perception of English language learners  towards  the use of social media  in  the  teaching learning activities especially for reading classroom. By using qualitative  research,  this  study  focuses on  learner’s perceptions towards social media assisted for language  learning  (SMALL) in reading classroom.  A total of   72 English language education learners  at  Universitas Pembinaan Masyarakat Indonesia participated in this study  through 5 point Likert scale survey  and interview. As the result, social media got positive perceptions from the learners. The dominant social media platform used was Instagram then following Youtube, Tiktok and Whatsapp. These learners believed that social media could be used as a tool for language learning that enhance  learners'  language skills especially reading and  engage  them  better  with lecturers and classmates in learning activities.